Asian Dust Particles Induce Macrophage Inflammatory Responses via Mitogen-Activated Protein Kinase Activation and Reactive Oxygen Species Production. (28th May 2014) - Higashisaka, Kazuma; Fujimura, Maho; Taira, Mayu; Yoshida, Tokuyuki; Tsunoda, Shin-ichi; Baba, Takashi; Yamaguchi, Nobuyasu; Nabeshi, Hiromi; Yoshikawa, Tomoaki; Nasu, Masao; Yoshioka, Yasuo; Tsutsumi, Yasuo
Abstract : Asian dust is a springtime meteorological phenomenon that originates in the deserts of China and Mongolia. The dust is carried by prevailing winds across East Asia where it causes serious health problems. Most of the information available on the impact of Asian dust on human health is based on epidemiological investigations, so from a biological standpoint little is known of its effects. To clarify the effects of Asian dust on human health, it is essential to assess inflammatory responses to the dust and to evaluate the involvement of these responses in the pathogenesis or aggravation of disease. Here, we investigated the induction of inflammatory responses by Asian dust particles in macrophages. Treatment with Asian dust particles induced greater production of inflammatory cytokines interleukin-6 and tumor necrosis factor- α (TNF- α ) compared with treatment with soil dust. Furthermore, a soil dust sample containing only particles ≤10 μ m in diameter provoked a greater inflammatory response than soil dust samples containing particles >10 μ m. In addition, Asian dust particles-induced TNF- α production was dependent on endocytosis, the production of reactive oxygen species, and the activation of nuclear factor- κ B and mitogen-activated protein kinases. Together, these results suggest that Asian dust particles induce inflammatory disease through the activation of macrophages.